2019
DOI: 10.1017/nws.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Values in adolescent friendship networks

Abstract: Values—the motivational goals that define what is important to us—guide our decisions and actions every day. Their importance is established in a long line of research investigating their universality across countries and their evolution from childhood to adulthood. In adolescence, value structures are subject to substantial change, as life becomes increasingly social. Value change has thus far been understood to operate independently within each person. However, being embedded in various social systems, adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…During people's childhood, boys and girls develop different social value orientations, either by nature or nurture (see [12] for a review). Driven by the large proportion of same-sex friendships (e.g., [41,42]), these differences become more pronounced during childhood and early adolescence [12]. With the end of school education, gender segregation declines [43], and so SVO harmonizes between genders.…”
Section: Discussionmentioning
confidence: 99%
“…During people's childhood, boys and girls develop different social value orientations, either by nature or nurture (see [12] for a review). Driven by the large proportion of same-sex friendships (e.g., [41,42]), these differences become more pronounced during childhood and early adolescence [12]. With the end of school education, gender segregation declines [43], and so SVO harmonizes between genders.…”
Section: Discussionmentioning
confidence: 99%
“…In total, the dataset consisted of four groups, that is, two age cohorts in two countries. Appendix 1 includes more detailed information on the composition of the sample (for further details and documentation, see also Kindschi et al (2019) and Becker et al (2020)).…”
Section: Datamentioning
confidence: 99%
“…At the same time, friendship in this period has an impact on adolescent's many aspects such as his/her formation of values, choice of profession, and the development of identity (Döğücü 2004;Wang & Gu, 2019). For example, Kindschi et al (2019) found that adolescents' value systems evolve in a continuous cycle of internal validation through the selection and enactment of goals-thereby experiencing both congruence and conflicts-and external validation through social comparison among their friends.…”
Section: Introductionmentioning
confidence: 99%